Dampak Toksisitas Limbah Industri Tekstil Terhadap Kualitas Air dan Biota Akuatik - Syalwa Arsa; Ulli Zahrati; Firdus Firdus; Muhammad Nasir; Alia Rizki (INDO PUBLISHING, 2026)
The development of the textile industry makes a significant contribution to the economy, but its production activities also generate large amounts of liquid waste that has the potential to pollute aquatic environments. Textile industrial waste generally contains various hazardous substances such as synthetic dyes, organic chemicals, surfactants, and heavy metals like chromium, which can degrade water quality and cause toxic effects on aquatic organisms. This article aims to analyze the performance of textile industrial waste, examine its effects on water quality parameters, and assess its toxicity to aquatic biota. The method used is a literature review of various scientific journal sources related to textile waste and its impact on marine ecosystems. The results show that textile waste can increase BOD, COD, turbidity, and suspended solids content, thereby reducing dissolved oxygen levels in water. This condition can cause physiological stress, growth disorders, and even death of aquatic organisms. Furthermore, heavy metals and synthetic dyes in textile waste have the potential to bioaccumulate and biomagnify in the food chain, threatening the balance of marine ecosystems and human health. Therefore, effective management and treatment of textile industrial waste is crucial to reduce the impact of pollution and protect the aquatic environment.